For a typology of the metafictional procedures in contemporary lyrics - Pérez Bowie, José Antonio (Tropelías: Review of Literary Theory and Comparative Literature, 2019)
First of all the paper tries to revise the concept of "metafiction" and to fix the two main senses: the evidence of the literary communication fictionality and the self-referential element of literary discourse. Secondly, ir offers a summary of the main proposals for the discussion about the fictional aspects of lyrical discourse; without any personal preference, I admit that the word "metafictional" can be applied to that discourse when referring to the detachmentfrom those conventional patterns by which lyrical communication is ruled. Thirdly, there is a description of the mechanisms of detachment from the pattems which can be observed in contemporary Spanish Poetry and which are illustred with reference to various examples.
Keywords: Lyrical poetry; Metafiction; Contemporary spanish poetry